Churches in the Irish Landscape AD 400–1100 - Pickles, Thomas (Medieval Settlement Research, 2023)
A deceptively straightforward premise underpins this wonderful book: that, for any church, ‘…regardless of the historical or archaeological information available for the site itself, its position in the landscape can reveal a lot’ (p.2) The sophisticated conceptual approaches informing the analysis are introduced with an enviably light touch. Using Pierre Bourdieu on the relationship between structures and actions, landscapes are considered social arenas in which religious identities are negotiated while disposing of the dead, assembling, worshipping or processing the resources necessary to support such activities. Inspired by Clifford Geertz, thick descriptions are pursued, because landscapes are ‘the wider canvas on which the activities, or fields of discourse, that take place within and between sites and locales are bound together into absorbing and dynamic social worlds’ (p.5). Echoing recent work on religious beliefs, religious landscapes are seen to collapse false dichotomies between orthodox, literate and clerical Christianity, and popular, magical or superstitious beliefs.